Potassium storage mechanism of In2S3/C nanofibers as the anode for potassium ion batteries. (20th December 2021) - Yang, Min; Su, Die; Zhang, Wen; Wen, Jiaxing; Liu, Wen; Luo, Qi; Liu, Li; Wang, Xianyou
Abstract: The excellent electrochemical performance of indium sulfide (In2 S3 ) in lithium ion batteries (LIBs) and sodium ion batteries (SIBs) prompted us to explore its energy storage mechanism in potassium ion batteries (PIBs). In this work, In2 S3 /C nanofibers are successfully synthesized by simple electrospinning and subsequent vulcanization. In K half cells, compared to commercial In2 S3 electrodes, In2 S3 /C nanofibers as anode materials for PIBs show outstanding electrochemical performance, which can deliver reversible capacities of 397.6 (25), 366.2 (50), 335.2 (100), 307.8 (200), 260.4 (500) and 212.2 mAh g −1 (1000 mA g −1 ), respectively. In K full cells, In2 S3 /C nanofibers can also show good potassium storage performance and can light up 15 light emitting diodes (LEDs). The superb electrochemical performance of In2 S3 /C nanofibers is due to the in-situ composite with self-nitrogen-doped carbon matrix and the nanoization of In2 S3 particles, which buffers the volume effect and improves the conductivity of the material during the potassium storage process. In addition, the mechanism of potassium storage of In2 S3 /C nanofibers was systematically studied by cyclic voltammetry (CV), ex-situ XRD, TEM and XPS methods. The mechanism of In2 S3 for K-ion storage can be described as the conversion reaction: In2 S3 + 6K + + 6e − ⇌ In + 3K2 S. Graphical abstract: Image, graphical abstract